Processing, microstructure and mechanical characterization of a new magnesium based multicomponent alloy. (2020) - Tun, K.S.; Nahata, Anchal; Vincent, S.; Gupta, M.
Abstract: In the present study, a new magnesium based multicomponent alloy consisting of five alloying elements was synthesized using the technique of Disintegrated Melt Deposition (DMD). Most of the conventional Mg based alloys have one dominant principle element with a small amount of other alloying elements. In this work, the alloy having a chemical composition of Mg70 Al18 Zn6 Ca4 Y2 (atomic pct.) was designed by incorporating multiple alloying elements (Al, Zn, Ca and Y) with high amount of alloying element concentration (2 to 18 atomic pct.) into principle element, Mg. Investigations were done on the microstructure and mechanical properties of the developed alloy. The formation and presence of phases and microstructural evolution of the alloy were examined using scanning electron microscopy, energy dispersive x-ray (EDX) analysis and x-ray diffraction (XRD) analysis. The mechanical properties of the developed alloy was determined by way of hardness tests and compression testing. Significantly high macrohardness (59 HRB) and microhardness (150 HV) was realized in Mg70 Al18 Zn6 Ca4 Y2 multicomponent alloy. The measured hardness values in this alloy was much higher when compared to those of commercial Mg alloys.